Avulsed Anterior Permanent Tooth Replaced by Fixed Functional Interim Prosthesis with Natural Crown: A Case Report - Pal, Ananya; Dev, Shankhanil; Zahir, Shabanam; Kundu, Gauatm Kumar (Journal of Dentistry Indonesia, 2019)
The incidence of trauma to the anterior teeth is a common occurrence in children. From the very moment the child tries to walk erect independently, the susceptibility of the child’s anterior teeth getting injured begins. Avulsion (a type of traumatic injury) is the complete loss of the tooth from its socket. Various treatment modalities are available to treat such accidents. The tooth can be replanted back or replaced by a prosthesis, it depends upon the extraoral drytime and the stage of development of root of the avulsed tooth. The present case-report describes the way in which an avulsed permanent maxillary central incisor of a 12 year old boy was replaced aesthetically, and satisfactorily after 1 month of avulsion by means of a biological fixed functional prosthesis ( a modified “Hollywood Bridge” ) where the crown of the avulsed tooth was used as a pontic and stainless steel wires and bands were used to fix the prosthesis in the mouth as an interim treatment option.